Relationship Between Mother’s Education Level and Social Development of Children Aged 1–3 Years - Nur Mufida Alfi; Elva Febri Ashari; Firdha Amaliatus Sholihah (Universitas Nurul Jadid Paiton Probolinggo, East Java, Indonesia, 67291, 2025)
The quality of today's children is a determinant of the quality of human resources in the future. Baby's brain growth is influenced by environmental factors, including stimulation, as well as parenting. Growth is said to be too late if a child does not reach the stage of growth and development that is expected at the proper age.Of this research determined the relationship between maternal education level to the social development of children aged 1-3 years in Alas sumur Kulon village district of Kraksaan Probolinggo.This research used the correlation analytic research with cross sectional approach. The total sample were40 mothers and children. The sampling technique by using total sampling. The collection of data collected through observation and interviews with aid DDST sheet. That was analyzed by using the Spearman rank test.Obtained in this research, there is a relationship between maternal education level of the child's social development. From the test results obtained Spearman rank p = 0,000 r = 0.538 with a force that showed a positive direction (+).Of this study is an association between maternal education level to the social development of children aged 1-3 years in Alas sumur Kulon village district of Kraksaan Probolinggo.